An analysis of Technological, Pedagogical, and Content Knowledge (TPACK) competencies of mathematics teachers in Sumatra in terms of gender - Sepriyanti, Nana; Aniswita, Aniswita; Wahida, Deni (Indonesian Journal of Science and Mathematics Education, 2024)
This research aims to analyze the TPACK competencies of mathematics teachers in Sumatra based on gender differences. Using a sequential explanatory mixed method approach, this study collected data through questionnaires and interviews to test hypotheses using two-way analysis of variance (ANOVA). The results indicate that mathematics teachers in Sumatra have a high level of TPACK competencies, with gender influencing the pedagogical knowledge and content knowledge domains. Specifically, male teachers exhibit higher competency in these domains compared to their female counterparts. Additionally, male teachers more frequently utilize technology in teaching and exhibit greater variability in integrating TPACK compared to female teachers. The implication of this research provides valuable insights for the development of teacher training programs that consider gender factors in enhancing TPACK competency, which is crucial for effective technology integration in mathematics education.